2003
DOI: 10.1007/s00423-003-0418-y
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus granulosus infection: clinical presentation, medical treatment and outcome

Abstract: The recent ultrasound WHO consensus classification of hepatic cysts is a major achievement, since on the basis of this classification prospective clinical trials can be initiated. The results of such studies may provide the basis for a stage-specific appropriate medical, interventional or surgical therapy, or even guide the clinicians to opt for 'watch and wait' by close observation without specific treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
97
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 28 publications
2
97
0
9
Order By: Relevance
“…Echinococcus is not excluded by negative serology, late echinoccocal cysts may appear partly solid, or partially or fully calcified, displaying a similar morphology as in our case [8]. In late or inactive echinococcal cysts, antihelminthic treatment is not indicated, and the decision for a surgical option is guided by symptoms of the patients [8]. Diagnosis of peritoneal tuberculosis is less straightforward because the radiological morphology is unspecific [2,7].…”
Section: Discussionmentioning
confidence: 84%
“…Echinococcus is not excluded by negative serology, late echinoccocal cysts may appear partly solid, or partially or fully calcified, displaying a similar morphology as in our case [8]. In late or inactive echinococcal cysts, antihelminthic treatment is not indicated, and the decision for a surgical option is guided by symptoms of the patients [8]. Diagnosis of peritoneal tuberculosis is less straightforward because the radiological morphology is unspecific [2,7].…”
Section: Discussionmentioning
confidence: 84%
“…Traditionally, the treatment of echinococcosis relies primarily on surgery and/or chemotherapy, and the treatment strategy depends largely on different factors, such as metacestode size and location, viability status, the interaction between the expanding parasite and the adjacent host tissue, complicating bacterial or fungal infection and potential complications related to cyst rupture and spillage of protoscoleces (Kern, 2003(Kern, , 2006.…”
Section: I M I T a T I O N S O F C U R R E N T C H E M O T H E R A mentioning
confidence: 99%
“…A study comprised of 3282 echinococcosis patients treated with ABZ showed that most side-effects were associated with the gastrointestinal tract (Pawloski, 1997 ;Kern, 2003), but no fatal cases involving ABZ therapy have been described. In 3 .…”
Section: I M I T a T I O N S O F C U R R E N T C H E M O T H E R A mentioning
confidence: 99%
“…For many years, the preferred treatment strategy for CE has been radical resection of the parasite mass (Kern, 2003(Kern, , 2006. Other options include imageguide percutaneous treatment (PAIR=puncture, aspiration, injection, reaspiration) (Brunetti et al 2004) and chemotherapy (El-On, 2002).…”
Section: E C H I N O C O C C U S: B I O L O G Y a N D D I S E A S Ementioning
confidence: 99%